Propuesta de sistema de gestión ambiental bajo la norma ISO 14001 para la Reserva Natural Punta Gorda, Bahía de Caráquez - Santos Mera, Yemelin Raquel (2021)
The objective of the research is to properly design a proposal for an Environmental Management System based on the International Standardization Organization standards (ISO) 14001 for the Punta Gorda Natural Reserve in Bahía de Caráquez. Internship activities, research tourism, eco-tourism, hiking, camping, lodging, among others, are carried out. The environmental components of the nature reserve reflect a variety of mammals and birds. The climatological description illustrates rainfall that fluctuates 500-750 mm, temperature ranging feom 24-26 ° F, 100m contour lines, and geology mostly has tobaceous sandstone soils categorized as a dry mega-thermal tropical climate. The elaboration of the environmental policy involved the commitment to maintain control and management of the environmental aspects that occur, especially of a significant nature. The legal matrix based on the Kelsen pyramid was developed. The procedures contemplated were identification of impacts - environmental aspects, legal matrix, scheduled inspections, scheduled audits, Good environmental practices, Solid Waste Management and training based on that required by the ISO 14001 standard. An environmental policy with a level of responsibility and contemplating the environmental requirements and objectives, which contributes to the conversation of the components of the Punta Gorda Natural Reserve theoretical reasons and procedures, instructions, records for proper environmental management.